2011
DOI: 10.1097/mpg.0b013e31820ba46c
|View full text |Cite
|
Sign up to set email alerts
|

Do Children With IBD Really Respond Better Than Adults to Thiopurines?

Abstract: Background and Objectives: Children and adolescents with inflammatory bowel disease (IBD) have more extensive and severe disease than adults. Despite a lack of comparative studies, thiopurines are frequently cited as being more efficacious in children. To test this assertion, we compared the efficacy of thiopurines in children with IBD with that in adults matched for disease phenotype. Patients and Methods: Fifty paediatric and adult patients with IBD started on a thiopurine were matched for sex, disease type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…As the disease severity in both groups was similar at diagnosis, the increased radiation exposure in Group B may be related to longer duration of disease and follow-up, diagnosis of IBD before the routine use of magnetic resonance enterography, increased surgery rates, and increased hospitalizations. Goodhand et al [29] noted the value of the dedicated adolescent and young adult service in facilitating the reduction of radiation exposure in their cohort. The direct impact of the transition clinic on reduction in radiation exposure in our study is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 98%
“…As the disease severity in both groups was similar at diagnosis, the increased radiation exposure in Group B may be related to longer duration of disease and follow-up, diagnosis of IBD before the routine use of magnetic resonance enterography, increased surgery rates, and increased hospitalizations. Goodhand et al [29] noted the value of the dedicated adolescent and young adult service in facilitating the reduction of radiation exposure in their cohort. The direct impact of the transition clinic on reduction in radiation exposure in our study is difficult to ascertain.…”
Section: Discussionmentioning
confidence: 98%
“…Notwithstanding the extensive experience with immunomodulators, long-term efficacy data in children are scarce and have focused often only on the short-term steroid sparing effects [38][39][40][41][42][43][44][45][46]. The efficacy of azathioprine in CD patients was demonstrated by Riello et al in a retrospective study, showing that steroid-free remission was achieved in 29/93 (31.2%) two years after start [39].…”
Section: Discussionmentioning
confidence: 99%
“…Increased efficacy of 6-MP/AZA in the pediatric population was suggested by the Markowitz study,10 where it was hypothesized that treatment earlier in the course of the disease may be a potential disease-modifying strategy 22. Another possible explanation for the longer treatment continuation among children observed here is that children may experience less toxicity than adults, as has been suggested by a small, single-center retrospective study by Goodhand et al,14 which found that 6-MP/AZA was better tolerated in children than adults (albeit with no difference in efficacy). Finally, nonmechanistic reasons may also explain the elevated continuation in children, where parents’ involvement in the management of their child’s disease may improve adherence.…”
Section: Discussionmentioning
confidence: 62%
“…However, data from more recent studies examining the real world use of 6-MP/AZA have suggested that the clinical effectiveness of thiopurines in practice may be less than the efficacy demonstrated in clinical trials. A study by Goodhand et al14 reported that 6-month steroid-free remission was achieved in only 30% (15/50) of children and 38% (19/50) of adults treated with thiopurines. Another study, by Riello et al,15 found similar rates of steroid-free remission in a small, single-center observational pediatric cohort of CD patients.…”
Section: Introductionmentioning
confidence: 99%